THE ISSUES OF LEARNING ENGLISH FOR SPECIFIC PURPOSE IN THE ERA DIGITAL REVOLUTION: TEACHING MATERIALS FOR STUDENTS IN HIGHER EDUCATION INDONESIA - Indrapuri, Sri Ayu; Mahdum, Mahdum; Azhar, Fadly; Erni, Erni; Daud, Afrianto (Universitas Dharmawangsa, 2025)
Mastery of English language competence is a demand for non-English study program students. The purpose of this study is to determine the problems of learning English as ESP (English for specific purpose) in the development of teaching materials for students. This research methodology uses qualitative through systematic literature review. The results of this study are problematic in English learning of ESP are the Lecturers face difficulties in developing ESP materials that are in accordance with student needs and the obstacle of obtaining ESP textbooks which relevant to work field of students. Solutions to overcome the problem of learning special English (ESP) in students in the Digital Revolution era involve industry-relevant curricula, the use of digital technology, interactive and contextual content, collaboration with industry, Soft skills development, Project-based learning, comprehensive evaluation, a student-centered approach, and psychological and technical support for students who need it.